Study of Possible Changes in Lipid Profiles between Premenopausal and Postmenopausal Women with Hyperthyroidism and Others with Hypothyroidism - Hussain, Zainab Khidhair (Iraqi Journal of Science, 2022)
Menopause is the lack of menstrual cycle for at least six months. Due to hormonal changes, the alternation of lipid profile as a risk factor related to heart disease increases during menopause . One hundred twenty Iraqi women, aged between 40-65 years, were selected for this study. They were divided into two groups: 60 premenopausal and 60 postmenopausal women, and then each group was further divided into two subgroups: 20 women with hyperthyroidism and 20 with hypothyroidism, as well as 20 healthy women as control group. Blood samples were collected to estimate  hormonal parameter by enzyme linked immunosorbent assay (ELISA) and lipid profile using enzymatic technique. The results showed that alterations in lipid profile included decrease in the cholesterol levels, triglyceride, LDL and VLDL. Whereas HDL increased in hyperthyroidism as compared to hypothyroidism and control groups in premenopausal women. In women with postmenopause, alterations of lipid profiles included a decrease in the cholesterol level, triglyceride, high density lipoprotein (HDL), very low density lipoprotein (VLDL) except an increase in low density lipoprotein (LDL) in hyperthyroidism as compared to hypothyroidism and control groups. Also, the level of lipid profiles increased in hypothyroidism rather than hyperthyroidism both in pre and postmenopause. According to this study, the conclusion was reached that there was an increase in the lipid profile level in postmenopausal women than premenopausal women with hypothyroidism when compared to hyperthyroidism.